Studies Studies on the phytochemicals of clove and their biological activities - Hema Krishna, R (International Journal of Advanced Chemistry, 2024)
Cloves are a fragrant spice made from the dried flowers of the clove tree. In the past, spices used to be worth their weight in gold, and cloves were no exception. Today, cloves remain a popular spice that gives many dishes subtly sweet warmth. A drop of clove oil is 400 times more powerful as an anti-oxidant than wolf berries or blueberries. Cloves contain a lot of manganese, a mineral that helps your body manage the enzymes that help repair your bones and make hormones. Manganese can also act as an antioxidant that protects your body from harmful free radicals (unstable atoms that cause cell damage). Cloves are a fragrant, dense spice that can be added to both savory dishes (such as curries) and sweet desserts (such as pumpkin pie). They're full of powerful nutrients that help protect your cells from damage. Some natural compounds in cloves interfere with medicines or cause side effects that can be life-threatening. So, it's safest to only cook or bake with cloves and enjoy this spice's health benefits that way. Clove is utilized in cosmetics, medicine, gastronomy, and agriculture due to its abundance of bioactive components such as gallic acid, flavonoids, eugenol acetate, and eugenol. Clove essential oil has been revealed to have antibacterial, antinociceptive, antibacterial activities, antifungal, and anticancerous qualities. Anti-inflammatory chemicals, including eugenol and flavonoids, are found in clove that help decrease inflammation and alleviate pain. The anti-inflammatory and analgesic qualities of clove oil have made it a popular natural cure for toothaches and gum discomfort. Due to its therapeutic potential, it has been used as a bioactive ingredient in coating fresh fruits and vegetables. This research article outlines the potential food processing applications of clove essential oil. The chemical structures of components, bioactive properties, and medicinal potential of clove essential oil, including phytochemical importance in food, have also been thoroughly addressed.